FTA contributes to Indonesia's establishment of a Strategic Coordination Team for Wetlands Management to achieve Sustainable Development Goals and Low Carbon Development - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
FTA project is working group member of the Strategic Coordination Team set up by the Ministry of National Development Planning/National Development Planning Agency of Indonesia.